Study of Superconductivity in Li based binary alloys of alkali metals using HFP Pseudopotential Technique - Chowdhary, Sunil Kumar (Innovative Research Thoughts, 2018)
By using technique of Harrison’s First Principle Pseudopotential we studied superconductivity in binary alloys of Li with other alkali metals. Historically HFP Pseudopotential method has been rarely used. Unique opportunity is explored to use HFP Pseudopotential technique to study SSP like of alkali metal alloys of Li. SSP of Li and Li based binary alloys of alkali metals at varying concentration 0.9 to 0.1 were computed through McMillan’s formalism (1968). V-S form of screening is used in present work for obtaining SSP of Li based alkali metal binary alloys. As a variant SSP are studied using three different forms of eigenvalues of Herman-Skillman (HS), Hafner (H) and Clementi (C). Comparison of present values of SSP with available experimental and theoretical findings by other scholars are highly encouraging. Further, results computed in our present work will enrich the data bank for SSP of alkali-alkali binary alloy.